Bnaslawa environmental parameters planning modelling - Shuokr Qarani Aziz (Reciklaža i Održivi Razvoj)
Global warming, climate change, greenhouse gasses, floods, drought years, and desertification have an impact on the environment. Naturally, the environment of Bnaslawa district (Dashti Hawler) in Erbil City-Iraqi Kurdistan region is affected by the global environmental changes. This research focused on the assessment of environmental parameters, planning, and environmental modelling in Bnaslawa district. A series of site visits, interviews, collection of documented data from directories and literature were conducted for data collection. Environmental factors such as wind direction, topography, water sources, soil type, distance, archeology, esthetics, air pollution, noise pollution, and disease spread were selected. The selected points for environmental planning were landfill, gas factory, slaughterhouse, quarry, cemetery, wastewater treatment plant, green area, animal shelters, industrial area, commercial area, institutional area, and service area. The points for the environmental factors were changed from zero (low impact) to 10 (strong/high impact). The ratio of points and twelve mathematical models for the elements were determined. Based on the scoring and mathematical models, wind direction, topography, water sources, archeology, esthetics, air pollution, noise pollution, and disease spread had an excessive impact on the planning and management of environmental parameters. In contrast, soil type and distance had less influence.